Die Bedeutung Israels im christlichen Verständnis: Karl Barths Israel(ein)sicht von 1946 - Schelhas, Johannes (Zeitschrift für katholische Theologie, 2008)
According to Karl Barth Israel is a complex theological and historical reality. It means (1) the Jewish people as the origin of Jesus of Nazareth, (2) the people of the Old Testament in covenant with Yhwh, and (3) the Jewish folk of history and of our present post-Biblical times. In the faith of the Jews the election of Israel is still alive even post Christum crucifixum. Owing to the covenant with Abraham Israel has a mission for humankind and this mission is through Jesus still effective. The category of mission can be fruitful in the systematic discussion conceming the relationship of Jews and Christians. Furthermore, Barth exhibits how a biblical typology can be understood in terms of dialogue.